BIOAKTIVITAS EKSTRAK ETANOL BUAH MENGKUDU (Morinda citrifolia L.) TERHADAP RAYAP TANAH (Coptotermes curvignathus Holmgren) - Pratiwa, Chandra; Diba, Farah; dina, Wah (Universitas Tanjungpura, 2015)
The study aims to determine the bioactivity of Noni fruit extracts against subterranean termites Coptotermes curvignathus and determine the optimum level of concentration of Noni fruit extract. Bioassay test using filter paper whichpreserved for 15 minutes at various concentration levels of Noni fruit extract. The concentration used was 2%, 4%, 6%, 8% and 10%. Bioassay tests were carried out for 21 days then mortality and filter paper weight loss was measured. The highest mortality was achieved on concentration 10% with resulted 100% mortality, and the lowest weight loss of filter paper was on concentration 10% with value 9.44%. The optimal concentration was 8%. Â Keyword: Coptotermes curvignathusÂ Ethanol extract, Morinda citrifolia L